Cancer with unknown primary: finding a needle in a hay stack - Giesel, Frederik L.; Mafomane, M. P.; Zechmann, Christian; Bergmann, Frank; Schemmer, Peter; Haberkorn, Uwe; Kratochwil, Clemens (Experimental oncology, 2012)
Detection and resection of small neuroendocrine tumours (NET) is like finding a needle in a hay stack. Use of specific tracers such as 68Ga-DOTATOC in a PET/CT